Identification and Validation of Synthetic Phenolic Antioxidants in Various Foods Commonly Consumed in Malaysia by HPLC - Chen Son Yue; Wai Lun Hong; Sheri-Ann Shu Wei Tan; Khye Er Loh; Yee Chuan Liew; Rosemary Elizabeth Yap; Zi Yi Chong; Jiong Chen Chai (Indonesian Journal of Chemistry, 2019)
This study was conducted in order to identify the presence of four synthetic phenolic antioxidants (SPAs): propyl gallate (PG), tert-butylhydroquinone (TBHQ), butylated hydroxyanisole (BHA), and butylated hydroxytoluene (BHT) in various food stuffs that are commonly consumed in Malaysia. The identification method was optimized and validated before it was applied to the analyses of eighty three food samples which include chewing gum, chili sauce, cereal-based snack food, noodles, potato snack, cereal breakfast, oat, biscuit, cookie, coffee, junk food, seaweed, nut, chocolate, apple juice, orange juice and blackcurrant juice. Twenty nine food samples contained SPAs either singly or in combination. The chromatography conditions such as elution method, flow rate and wavelength were optimized. Good linearity ranges (1–300 mgL–1) were found for all the four phenolic antioxidants. RSD for repeatability and reproducibility ranged from 0.15–0.84% for both precision analyses. LOD and LOQ ranged from 0.02–0.67 and 0.06–2.03 mgL–1, respectively. Recoveries of the four SPAs ranged from 80.4 to 119.0% when selected food items spiked at 10, 50, and 100 mgL–1.